PERAN ROH KUDUS DALAM SAKRAMEN KRISMA, PENGURAPAN ORANG SAKIT DAN IMAMAT - Yanto, Stepanus Yedi; Firmanto, Antonius Denny; Aluwesia, Nanik Wijiyati (STIPAS Keuskupan Agung Kupang, 2023)
Sacraments are signs given by Jesus to His people. Through the sacraments, humans are reunited with God. In Catholicism there are seven sacraments. Each sacrament has different graces and meanings. In this research, the author used descriptive qualitative research methods using data analysis. In qualitative research methods, the subject's perspective is emphasized more. The author analyzes these data through literature study. The result of this research is that through the sacrament of chrismation, our relationship with the Church is increasingly perfected because of the special power of the Holy Spirit. The grace of the sacrament of anointing of the sick makes the sick person strengthened and united with the suffering of Jesus Christ. Through the grace of the sacrament of priesthood, the Hierarchs have the special power topresent the body and blood of Christ in the celebration of the holy eucharist.